In de RAI. V.l.n.r. : Ter Beek, Vellenga, Meijer, Van der Louw, daarachter Klein, rechts van hem Sajet - Iburg, Lida,
In de RAI. V.l.n.r. : Ter Beek, Vellenga, Meijer, Van der Louw, daarachter Klein, rechts van hem Sajet.